The Effect of Compensation and Work Motivation on Employee Performance with Job Satisfaction as an Intervening Variable - Akhmad Khusnan; Tristiana Rijanti (Badan Penerbit STIEPARI Press, 2025)
This research aimed to describe and analyze the influence of compensation, work motivation, and job satisfaction on employee performance at the Batang Regency Regional Secretariat. A purposive sampling method was used to select 140 respondents for this study. Data collection was conducted using a questionnaire with a 7-point Likert scale. The instruments were tested for validity and reliability. Validity testing was carried out through factor analysis, which examined the Kaiser-Meyer-Olkin (KMO) and factor loading values to determine sample adequacy. Reliability was assessed using Cronbach’s alpha to ensure consistency of the measurement. Hypothesis testing was performed using multiple linear regression with SPSS version 27 and the Sobel Test software. The results of the study revealed several significant findings. First, compensation was found to have a positive and significant effect on job satisfaction, suggesting that employees who are well-compensated tend to be more satisfied with their jobs. Second, work motivation was also found to have a positive and significant effect on job satisfaction, indicating that motivated employees are likely to feel more satisfied in their work environment. Third, compensation was shown to have a positive and significant effect on employee performance, highlighting that adequate compensation contributes to improved performance levels. Similarly, work motivation had a positive and significant effect on employee performance, demonstrating that motivated employees tend to perform better in their roles. Additionally, job satisfaction had a positive and significant effect on employee performance, suggesting that satisfied employees are more likely to deliver high-quality work. However, the study also found that job satisfaction does not mediate the influence of competence on employee performance or the influence of work motivation on employee performance. These findings suggest that while compensation, motivation, and satisfaction are crucial to performance, other factors may be at play in determining how competence and motivation directly influence performance outcomes.